Partnership model for small industry in cluster perspective in encouraging regional development (case study on some small industries in Jambi City) - Erfit Erfit; Yulmardi Yulmardi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
This study aims to analyze: 1) the profile of the small industry clusters in Jambi City, those are batik industry cluster, tofu/tempeh industry cluster and furniture industry cluster; 2) the collaboration/partnership between various business actors and other parties in small industry cluster in Jambi City works; 3) an effective partnership models for small industry clusters. This research is a collective case study (survey and case study). The analysis was carried out on the profile of the small industry cluster and the partnership between various industrial groups in the small industry cluster. The results of the study showed that Jambi City has potential for the development of small industries. It can be seen from the development of business and employment in small industries. Based on the partnership between industry groups, in Batik industry cluster and tofu/tempe industry cluster, it showed the existence of upstream partnership to the source of raw materials, downstream partnership to the consumers, and partnership with supporting industries. In terms of pattern, the partnerships are directed towards traditional partnerships which are based on trust. Meanwhile in the furniture industry cluster, there is no partnership at all, both upstream and downstream, as well as partnership with the supporting industries. However, the partnerships have not been effective. For this reason, it is necessary to build a partnership in small industry cluster that pays attention to the principle of mutual benefit, equality, legality, empowerment, and social capital.